A self-efficacy scale for measuring student progress in translation company simulations - Konttinen Kalle (Akademiai Kiado ZRt., 2022)
Applying factor analysis on survey data, this paper develops a concise scale of translation service provision self-efficacy aimed for diagnosing learning needs and assessing progress in pedagogical translation company simulations. First, a model of translation service provision activities based on the translation service provision standard ISO 17100 and a business process model of translation service is constructed and operationalized as a draft scale. The draft scale is then tested in an international survey (n = 380) conducted in connection with translation company simulation courses in university-level translator education. Exploratory factor analysis is used to identify dimensions and adequate items for a concise scale that comprises two four-item subscales: a project management self-efficacy subscale and a translation-production self-efficacy subscale. The scale is validated through confirmatory factor analysis. It is expected to be useful as a light-weight measurement instrument for frequent testing or as a compact part of more extensive scales.